2014
DOI: 10.3762/bjoc.10.260
|View full text |Cite
|
Sign up to set email alerts
|

Electrocarboxylation: towards sustainable and efficient synthesis of valuable carboxylic acids

Abstract: SummaryThe near-unlimited availability of CO2 has stimulated a growing research effort in creating value-added products from this greenhouse gas. This paper presents the trends on the most important methods used in the electrochemical synthesis of carboxylic acids from carbon dioxide. An overview is given of different substrate groups which form carboxylic acids upon CO2 fixation, including mechanistic considerations. While most work focuses on the electrocarboxylation of substrates with sacrificial anodes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
136
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 136 publications
(177 reference statements)
1
136
0
2
Order By: Relevance
“…Recent advances on this front has been reviewed by De Vos and co-workers. 786 Electrochemical carboxylation usually involves the reduction of substrates and/or carbon dioxide, leading to the formation of carboxylate anions. Such reactions are commonly carried out using sacrificial anodes wherein the oxidative dissolution of anode materials provides the counterion while preventing the undesired oxidation of substrates or products.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…Recent advances on this front has been reviewed by De Vos and co-workers. 786 Electrochemical carboxylation usually involves the reduction of substrates and/or carbon dioxide, leading to the formation of carboxylate anions. Such reactions are commonly carried out using sacrificial anodes wherein the oxidative dissolution of anode materials provides the counterion while preventing the undesired oxidation of substrates or products.…”
Section: Cathodic Reductionmentioning
confidence: 99%
“…[6,7] Recently, Martin and co-workers developed an elegant protocol for site-selectivity tunable carboxylation via nickel hydride or nickelalactone formation for the extensive scope of unsaturated hydrocarbons, such as styrenes, alkenes and alkynes. [9] Therefore, the reduction reaction takes place in the absence of a reducing agent and the reducing power can be easily controlled by the applied potentials. This reactions are mainly driven by reductive electrical potential on a cathode electrode.…”
Section: Doi: 101002/advs201900137mentioning
confidence: 99%
“…[5,6] Recent reports have demonstrated that the elaborate design of organometallic nucleophiles is the primary requisite for modulation of site-selectivity and extension of substrates in carboxylation. [9] Therefore, the reduction reaction takes place in the absence of a reducing agent and the reducing power can be easily controlled by the applied potentials. [8] As an alternative approach, heterogeneously catalyzed electrochemical carboxylation has gained increasing attention.…”
mentioning
confidence: 99%
“…Unlike other reviews for similar means, the purpose of this article is to focus on the most recent advances for preparing carboxylic acid derivatives from unsaturated hydrocarbon backbones using Ni as well as the cheaper and more abundant Fe species in a homogeneous 45 Page 2 of 38 Top Curr Chem (Z) (2016) 374:45 manner, including mechanistic considerations, when appropriate. Therefore, other catalytic CO 2 functionalization processes of paramount importance such as the area of cyclic carbonates [19][20][21], polymer formation, production of methanol or formic acid [22][23][24], electrochemical methods [25], co-catalyzed carboxylations [26], carbonylation methods [27], or reductive carboxylations of organic (pseudo)halides [14-16, 28, 29], among others, are beyond the scope of this review.…”
Section: Introductionmentioning
confidence: 99%